Powdery Mildews on Lactuca Species – A Complex View of Host-Pathogen Interactions. (2nd January 2020) - Mieslerová, B.; Kitner, M.; Křístková, E.; Majeský, Ľ.; Lebeda, A.
Abstract: The present work summarizes important new information and results focused on powdery mildew occurring on the genus Lactuca from a growing body, including long-term research. This plant genus is host to at least three biologically and ecologically different genera of powdery mildew: Golovinomyces (U. Braun) Heluta, Podosphaera Kunze, and Leveillula G. Arnaud. The taxonomy, distribution, morphology, and biology of Golovinomyces bolayi, Podosphaera xanthii, Leveillula lactucae-serriolae, and L. lactucarum are also discussed, along with the threat they pose to Lactuca spp., as well as methods of control. A deeper understanding has only been obtained in the Lactuca spp. – Golovinomyces bolayi pathosystem. The results of 20 years of study into the occurrence of G. bolayi in wild L. serriola populations in the Czech Republic found that the percentage of L. serriola populations infected by G. bolayi (disease incidence) varied considerably between 29 and 75.2% over the reporting period. Although this powdery mildew appears to prefer warmer temperatures (about 20 °C) and lower precipitation, it is hard to discern a direct relationship between meteorological data and disease occurrence. Study of the pathogenic variability of G. bolayi isolates from the Czech Republic between 2008 and 2017 (on a unified and stable differential set of 13 genotypes of genus Lactuca spp.) confirmed that G. bolayi isolates represented different combinations of reaction patterns on the Lactuca spp. differential set. However, isolates virulent on all 13 genotypes (i.e. super-race) were recorded very sporadically. Moving forward, studies of the mechanisms and genetics of resistance are greatly needed.